Proteomic Analysis Demonstrates Adolescent Vulnerability to Lasting Hippocampal Changes Following Chronic Alcohol Consumption - Hargreaves, Garth A.; Quinn, Heidi; Kashem, Mohammed A.; Matsumoto, Izuru; McGregor, Iain S. (Alcoholism, clinical and experimental research, 2009)
Background:  Excessive teenage alcohol consumption is of great concern because alcohol may adversely alter the developmental trajectory of the brain. The aim of the present study was to assess whether chronic intermittent alcohol intake during the adolescent period alters hippocampal protein expression to a greater extent than during adulthood. Methods:  Adolescent [postnatal day (PND) 27] and adult (PND 55) male Wistar rats were given 8 hours daily access to beer (4.44% ethanol v/v) in addition to ad libitum food and water for 4 weeks. From a large subject pool, subgroups of adolescent and adult rats were selected that displayed equivalent alcohol intake (average of 6.1 g/kg/day ethanol). The 4 weeks of alcohol access were followed by a 2‐week alcohol‐free washout period after which the hippocampus was analyzed using 2‐DE proteomics. Results:  Beer consumption by the adult group resulted in modest hippocampal changes relative to alcohol naïve adult controls. The only changes observed were an up‐regulation of citrate synthase (a precursor to the Krebs cycle) and fatty acid binding protein (which facilitates fatty acid metabolism). In contrast, adolescent rats consuming alcohol showed more widespread hippocampal changes relative to adolescent controls. These included an increase in cytoskeletal protein T‐complex protein 1 subunit epsilon (TCP‐1) and a decrease in the expression of 10 other proteins, including glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), triose phosphate isomerise, alpha‐enolase, and phosphoglycerate kinase 1 (all involved in glycolysis); glutamate dehydrogenase 1 (an important regulator of glutamate); methylmalonate‐semialdehyde dehydrogenase (involved in aldehyde detoxification); ubiquitin carboxyl‐terminal hydrolase isozyme L1 (a regulator of protein degradation); and synapsin 2 (involved in synaptogenesis and neurotransmitter release). Conclusions:  These results suggest the adolescent hippocampus is more vulnerable to lasting proteomic changes following repeated alcohol exposure. The proteins most affected include those related to glycolysis, glutamate metabolism, neurodegeneration, synaptic function, and cytoskeletal structure.